STEAM Education: Student Learning and Transferable Skills - Miralimovna, Malika Yunusova (International Journal on Human-Computing Studies, 2023)
The digital transformation of society taking place today entails radical changes not only in the economic but also in the social sphere, including education. The disappearance of a number of professions and the emergence of new ones is the main problem of the formation of professional skills in people, as well as the skills of self-education, self-development, intellectual mobility and teamwork. Under these conditions, it is necessary to search for innovative approaches to training personnel for the digital society. The article describes peculiarities of STEAM education and its benefits in the process teaching.